Effects of hybrid nanoparticle additives in n-butanol/waste plastic oil/diesel blends on combustion, particulate and gaseous emissions from diesel engine evaluated with entropy-weighted PROMETHEE II and TOPSIS: Environmental and health risks of plastic waste. (15th July 2022) - Yusuf, Abdulfatah Abdu; Dankwa Ampah, Jeffrey; Soudagar, Manzoore Elahi M.; Veza, Ibham; Kingsley, Ukoba; Afrane, Sandylove; Jin, Chao; Liu, Haifeng; Elfasakhany, Ashraf; Buyondo, Kasumba A.
Graphical abstract: Highlights: HC and CO emissions decreases for Hy60 fuels, and increasing NOx with Hy40 fuels. EC-soot slightly decrease compared to OC at all test fuels. PAHs and n-alkanes turned out to be more less at higher nanoparticles concentrations. In-cylinder pressure and HRR improve by 60 ppm hybrid nanoparticles. Abstract: Due to little industrial use of plastic waste recycling, over 200 million tons are thrown in landfills and more than 15 million tons end up in the ocean every year. This study aimed to investigate the effect of waste plastic pyrolysis oil, n-butanol, hybrid (Al2 O3 and TiO2 ) nanoparticles, and diesel fuel blends on combustion, gaseous emissions, and toxic particulates from CRDI diesel engine at steady-state mode. Experiments were carried out using different fuel ratios blended with hybrid nanoparticles at 20 ppm, 40 ppm, and 60 ppm through the ultra-sonification process. The most optimal blend was determined by Shannon entropy-weighted TOPSIS and PROMETHEE II, and was verified with the experimental results. The result shows that the overall fuels have a definite outline by naphthalene, which account for ∼42.67% of the total organic compounds. With n-bu15W30Hy60, n-bu20W40Hy40 and n-buW40Hy60 fuels, ∼54.9% significantly reduction was observed with n-alkane emissions. Low PAHs value found in particulate samples might reduce the effect of eyes irritants and cancers. Compared to EC, the variation in OC had unclear trend across all blend fuels, except for n-bu20W40Hy40 which averagely reduce by ∼89.47% across the Hy40 fuels. Reduction in CO and HC emissions were observed with Hy60 fuels, while the NOx of Hy40 tend to increase significantly than that of Hy20 and Hy60 by an average of 0.204 g/kWh and 0.401 g/kWh, respectively. However, almost equal pressure peaks were obtained with nano-fuels and their heat release became faster as the nanoparticles volume elevated. The MCDM results confirmed that significant benefit could be attained when the fuel mixtures are under the influence of nanoparticles at relatively higher concentrations. The short answer for waste plastic is to ban unnecessary uses of plastic, encourage alternative materials or fuels, and cut plastic production.